Ukraine : what went wrong and how to fix it - Aslund, Anders (Columbia University Press, 2015)
Ukraine suffered unprecedented political, economic, and military turmoil following Russia's annexation of Crimea in early 2014. Russian military aggression in the east and a legacy of destructive policies and corruption have created an imminent existential crisis for this young democracy. Yet Ukraine also has a great opportunity to break out of economic underperformance. In this study, Anders Aslund, one of the world's leading experts on Ukraine, traces Ukraine's evolution as a market economy starting with the fall of communism and examines the economic impact of its recent difficulties. Aslund argues that Ukraine must undertake sweeping political, economic, social, and government reforms to achieve prosperity and independence. For its part, the West must abandon its hesitant approach and provide broad economic assistance to help Ukraine transform itself.